Occurrence of Microplastics in the Asian Freshwater Environments: A Review - Farah Akmal, Idrus; Noradriena, Mohd Fadhli; Mohd Nasarudin, Harith (2022)
Microplastics pollution has become a worldwide common problem. Despite the growing numbers in researches regarding the microplastics, the understanding of microplastics in the freshwater environment are still less. This paper overviews the present knowledge and findings on the occurrence of microplastics in water and sediment of the freshwater environments in Asia. The review also covers the size distribution, polymers, morphological characteristics and sources of microplastics to the freshwater systems. Perspective of the adsorption of heavy metals on the microplastics to the freshwater systems are also discussed in this review